Gender diversity and chief executive officer tenure on earnings management - Harahap, Ida (Journal of Economics and Business Letters, 2025)
This study proves research that proves that differences between men and women can impact decisions. Several researchers have stated that men are risk-takers, whereas women are associated with natural risks and do not want to take risks that increase company performance. Agency problems increase as CEO approach retirement. In the last year of their tenure, CEO take advantage of their personal information to improve company performance to get higher compensation in the last year or after leaving work (retirement). The results of the regression analysis support the hypothesis that the representation of female CEOs negatively influences earnings management. These results indicate that the representation of female CEOs strengthens the quality of the earnings information presented in a company's financial statements. The regression analysis of the study supports the second hypothesis, which states that CEO tenure has a negative effect on earnings management. This shows that CEOs with long tenures are less aggressive in reporting earnings than those with short tenures.